BORDER AREA DYNAMICS : FACTORS AFFECTING THE IMPLEMENTATION OF TOPONYMY IN SANGIHE ISLANDS REGENCY - Bataha, Katerina (FISIP Universitas Malikussaleh, 2024)
This study aims to find out and analyze the factors affecting the implementation of toponymy policy and mapping areas in the Sangihe Islands Regency as a border area, along with findings on everything that affects the performance of these policies in an orderly effort of government administration and regional mapping. This research uses qualitative methods with a case study approach. The results showed that the factors that influenced the success of the toponymy implementation process in Sangihe Regency were communication, where communication had been carried out between the district work team to the Geospatial Information Agency and was supported by human resources as well as clarity of policy stand-ards and targets to make it easier for local governments through the district work team to implement toponymy policies in Sangihe. However, the research meeting shows that there are still some obstacles in this study, especially in the resource factor, namely the lack of surveyors and budget constraints.Penelitian ini bertujuan untuk mengetahui dan menganalisis faktor-faktor yang mempengaruhi implementasi kebijakan toponimi dan pemetaan wilayah di Kabupaten Kepulauan Sangihe sebagai wilayah perbatasan, beserta temuan tentang segala hal yang mempengaruhi kinerja kebijakan tersebut dalam upaya tertib penyelenggaraan kebijakan toponimi. administrasi pemerintahan dan pemetaan wilayah. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan bahwa faktor yang mempengaruhi keberhasilan proses implementasi toponimi di Kabupaten Sangihe adalah komunikasi, dimana komunikasi telah dilakukan antara tim kerja kabupaten dengan Badan Informasi Geospasial dan didukung oleh sumber daya manusia serta kejelasan standar dan target kebijakan untuk memudahkan pemerintah daerah melalui tim kerja kabupaten dalam mengimplementasikan kebijakan toponimi di Sangihe. Namun dari temu penelitian menunjukkan bahwa masih terdapat beberapa kendala dalam penelitian ini terutama pada faktor sumber daya yaitu kurangnya surveyor dan kendala anggaran.